The system of values of external and internal clients evidenced in the nursing process (Revista Latino-Americana de Enfermagem, 1999)
We shall understand value as a permanent belief on the specific way of conduct, or the final state of existence. Ours values influence many aspects of our lives. A distinction must be made betwen a person's own values and those values people attribute to objects and events in their inmediate environment. In this way, health exists as an end, or becomes a motivation to assure happiness or pleasure. It makes part of the system of values of an individual within the organization called hospital. We present an example such as to make us to reflect on how this value called health can be experienced and also on our own way of living and being healthy.